Interaction of human hemoglobin and semi-hemoglobins with the Staphylococcus aureus hemophore IsdB: a kinetic and mechanistic insight - Gianquinto, Eleonora (Sci Rep, 2019)
Among multidrug-resistant bacteria, methicillin-resistant Staphylococcus aureus is emerging as one of the most threatening pathogens. S. aureus exploits different mechanisms for its iron supply, but the preferred one is acquisition of organic iron through the expression of hemoglobin (Hb) receptors. One of these, IsdB, belonging to the Isd (Iron-Regulated Surface Determinant) system, was shown to be essential for bacterial growth and virulence. Therefore, interaction of IsdB with Hb represents a promising target for the rational design of a new class of antibacterial molecules. However, despite recent investigations, many structural and mechanistic details of complex formation and heme extraction process are still elusive. By combining site-directed mutagenesis, absorption spectroscopy, surface plasmon resonance and molecular dynamics simulations, we tackled most of the so far unanswered questions: (i) the exact complex stoichiometry, (ii) the microscopic kinetic rates of complex formation, (iii) the IsdB selectivity for binding to, and extracting heme from, α and β subunits of Hb, iv) the role of specific amino acid residues and structural regions in driving complex formation and heme transfer, and (v) the structural/dynamic effect played by the hemophore on Hb.